Governing uranium in Australia - Cindy Vestergaard (Danish Institute for International Studies (DIIS), 2015)
Australia has been a long-time key player in the global uranium market. Its uranium policy and regulatory structure has been surprisingly resilient since 1977 - a system that has endowed it with an international reputation for having created a uranium "gold" standard with non-proliferation at its centre. Today, Australias approach is being tested as it concludes an agreement to supply uranium to India - a state outside the Treaty on the Non-Proliferation of Nuclear Weapons (NPT). Its industry has also been affected by a struggling global uranium market where low spot prices have led companies to mothball a number of their mines. In 2014, Australia accounted for twelve per cent of world production, producing 5,000 tU which is the lowest for the country in sixteen years, This study analyses the Australian uranium supply industry, the evolution of its development, and the legal framework that regulates uranium production and trade in Australia. It is part of the larger Governing Uranium project led by the Danish Institute for International Studies (DIIS), which explores the dimensions of security of natural uranium in a changing global market. This report touches upon the evolution of Australias uranium policies, its uranium governance today and how it is adapting to a shifting global market.
Keywords: 300